Citizenship-Building in Early Childhood in Vulnerable Environments: Regarding the De Cero a Siempre strategy at Child Development Centers of the Colombian Institute for Family Welfare (2019)
The aim of this research was to identify how the state, family and society educate early childhood, in socially vulnerable environments, as citizens who respect human rights. This is achieved through the Child Development Center (CDI) program of the Colombian Institute for Family Welfare (ICBF) in accordance with the beliefs, experiences and concepts of individuals responsible for educating children, such as teachers, parents, and ICBF representatives. The research was conducted at the cdi Sol’Enfance; references include the cdi program documents and the theories of human rights and citizenship/social identity-building adopted by psychology in the social and community spheres. The research method was based on the theoretical-methodological proposal of social representations, which were retrieved by interviews, observations, and document review. All this was analyzed considering Bronfenbrenner’s ecological systems theory. The results allowed to offer purposeful criticism to the Child Development Centers program of the ICBF.